2003
DOI: 10.1159/000067012
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Di(2-ethylhexyl)phthalate in Humans during Pregnancy

Abstract: Background: Di(2-ethylhexyl)phthalate (DEHP), the most commonly used plasticizer, is a widespread ubiquitous environmental contaminant. The potential health hazards from exposure to DEHP and its main metabolite, mono(2-ethylhexyl)phthalate (MEHP), have been well documented. Exposure to DEHP and MEHP in humans at risk, such as pregnant women and human fetuses, has not been tested. Methods: Plasma DEHP and MEHP concentrations were measured in a total of 24 consecutive mother-infant pairs by high performance liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
63
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(66 citation statements)
references
References 13 publications
1
63
1
1
Order By: Relevance
“…Because the DEHP action depends on dose, time, and age (Latini 2000) and because DEHP effects are influenced by the stage of development at exposure among animals (Akingbemi et al 2001), the DEHP-related exposure risk is potentially higher for the developing fetus and newborn, particularly preterm. Recently, our preliminary findings indicated that the exposure to these environmental contaminants begins during intrauterine life, that these chemicals are able to cross the placental barrier, and that fetal exposure is closely related to maternal exposure (Latini et al 2003). The aim of this study was to measure concentrations of DEHP and/or its main metabolite, mono-(2-ethylhexyl)phthalate (MEHP), in a larger population of human neonates and to evaluate possible biologic effects from prenatal exposure to DEHP and/or MEHP.…”
mentioning
confidence: 98%
“…Because the DEHP action depends on dose, time, and age (Latini 2000) and because DEHP effects are influenced by the stage of development at exposure among animals (Akingbemi et al 2001), the DEHP-related exposure risk is potentially higher for the developing fetus and newborn, particularly preterm. Recently, our preliminary findings indicated that the exposure to these environmental contaminants begins during intrauterine life, that these chemicals are able to cross the placental barrier, and that fetal exposure is closely related to maternal exposure (Latini et al 2003). The aim of this study was to measure concentrations of DEHP and/or its main metabolite, mono-(2-ethylhexyl)phthalate (MEHP), in a larger population of human neonates and to evaluate possible biologic effects from prenatal exposure to DEHP and/or MEHP.…”
mentioning
confidence: 98%
“…A small thymic size at birth has also been reported in cases of histologic chorioamnionitis [2, 5, 12,14], while significant thymus and spleen atrophy in di(2-ethylhexyl) phthalate (DEHP)-treated mice has been described [15]. Very recently, DEHP exposure during pregnancy in humans has been documented [10]. Correlations between thymic size, chorioamnionitis and adverse outcome should be investigated in the future.…”
mentioning
confidence: 99%
“…Ftalati se unose u organizam ingestijom, inhalacijom i dermalnim izlaganjem tijekom cijelog života, ali i u vrijeme intrauterinog života (4,17,31). Dermalno i inhalatorno izlaganje ftalatima smatra se najčešćim putem unosa DEP-a koji je pronađen u higijenskim proizvodima kao što su sapun, šampon i kozmetika, ali je moguće i oralno izlaganje konzumacijom ilegalnih (neregistriranih) alkoholnih pića, u kojima se koristi kao sredstvo za denaturaciju etanola (5).…”
Section: Izloženost Ftalatimaunclassified